Combination therapy of dipeptidyl peptidase‐4 inhibitors and metformin in type 2 diabetes: rationale and evidence. Issue 2 (3rd June 2013) - Liu, Y.; Hong, T.
<x xml:space="preserve">Abstract</x> The main pathogenesis of type 2 diabetes mellitus (T2DM) includes insulin resistance and pancreatic islet dysfunction. Metformin, which attenuates insulin resistance, has been recommended as the first‐line antidiabetic medication. Dipeptidyl peptidase‐4 (DPP‐4) inhibitors are novel oral hypoglycaemic agents that protect glucagon‐like peptide‐1 (GLP‐1) from degradation, maintain the bioactivity of endogenous GLP‐1, and thus improve islet dysfunction. Results from clinical trials have shown that the combination therapy of DPP‐4 inhibitors and metformin [as an add‐on, an initial combination or a fixed‐dose combination (FDC)] provides excellent efficacy and safety in patients with T2DM. Moreover, recent studies have suggested that metformin enhances the biological effect of GLP‐1 by increasing GLP‐1 secretion, suppressing activity of DPP‐4 and upregulating the expression of GLP‐1 receptor in pancreatic β‐cells. Conversely, DPP‐4 inhibitors have a favourable effect on insulin sensitivity in patients with T2DM. Therefore, the combination of DPP‐4 inhibitors and metformin provides an additive or even synergistic effect on metabolic control in patients with T2DM. This article provides an overview of clinical evidence and discusses the rationale for the combination therapy of DPP‐4 inhibitors and metformin.